Financial Restructuring von Private Equity-Portfoliounternehmen - Das Lead-Advisor-Konzept als institutioneller Ansatz zur Restrukturierung von Distressed Investments - Batran, Karsten; Reinisch, Michael; Voigt, Kai-Ingo; Vučković, Daliborka; et al. (M&A Review, 2010)

How manufacturing firms navigate through stormy waters of digitalization: the role of dynamic capabilities, organizational factors and environmental turbulence for business model innovation - Witschel, Daliborka; Baumann, Dominik; Voigt, Kai-Ingo (Journal of Management & Organization, 2022)
Although research has shown that business model innovation (BMI) is an effective means to remain competitive in the digital age, many firms do not respond appropriately and often fail to exploit new digital opportunities. In this study, we adopt a microfoundational approach to understand the role and effects of dynamic capabilities (DCs) on BMI in the context of digitalization. Furthermore, we test how this relationship is influenced by contextual factors. Our results from a survey of German manufacturing firms demonstrate the importance of building strong DCs for effective BMI in the context of digitalization. We also highlight the advantages of an entrepreneurial leadership and mindset in this context. The study further suggests that environmental turbulence in the digital context acts as an antecedent to DCs and BMI, rather than moderating their relationship. While strategic factors indirectly affect BMI as antecedents of DCs, we found no evidence of an influence of the organizational structure.
CRIS-Team WoS Importer:2022-07-22

Knowledge Management in the Context of Industrial Service Innovation: Exploring the Effect of Selected Knowledge-based Determinants on the Innovation Performance - Vučković, Daliborka; Voigt, Kai-Ingo; Wolf, J. (European Conference on Intellectual Capital (ECIC), 2011)
LIM::247

On the Road to Successful Digitization: The Role of Dynamic Capabilities in Adopting and Implementing Digital Business Models – Insights from a Multiple-Case Study - Witschel, Daliborka; Döhla, Aaron; Kaiser, Maximilian; Pfletschinger, Thilo; Voigt, Kai-Ingo (Wissenschaftstagung 2018 der Erich-Gutenberg-Arbeitsgemeinschaft Köln e.V., „Value-creation and Innovation in the Digital Age“, 2018)

Riding on the wave of digitization: insights how and under what settings dynamic capabilities facilitate digital-driven business model change - Witschel, Daliborka; Döhla, Aaron; Kaiser, Merlin; Voigt, Kai-Ingo; Pfletschinger, Thilo (Journal of Business Economics, 2019)
Little is known what facilitates business model change in response to turbulent environments, particularly how firms can respond to digitization. This is noteworthy, since the emergence of digital technologies opens up the space for new business opportunities and at the same time creates numerous challenges. Motivated by the high practical relevance of the topic and following recent calls for investigating business model change from a dynamic capability lens, we show how and under what conditions firms successfully develop and implement digital business models. Our findings indicate, that firms need strong dynamic capabilities in order to respond to environmental dynamics. Further, we show first empirical insights about the role of organizational context as moderating variable on the relationship between dynamic capabilities and business model change. Dynamic capabilities are only effective, if there is an alignment between strategy, organizational design and appropriate leadership mindset. A further central outcome of the study is our contribution to an in-depth understanding related to the dynamic capability construct and their underlying mechanism. In doing so, we map overall 13 critical capabilities and various activities per case. We were also able to emphasize differences in the way of doing business in the digital age compared to the traditional view. First, we highlight the importance of relational capabilities. Internal networking, cross-divisional exchange and external partnerships increase the potential for a more efficient and effective implementation of digitization initiatives. Second, we distinguish between general and new digital capabilities. This specification allows managers to balance which capabilities to adapt, develop or build up in view of the given requirements on their road to successful digitization.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Business model adaptation; Business model change; Business model innovation; Dynamic capabilities; Environmental turbulence; Organizational design; Response to digitization; Strategy

Schlüsselfähigkeiten für die Entwicklung digitaler Geschäftsmodelle - Ergebnisse einer empirischen Fallstudienanalyse - Witschel, Daliborka; Döhla, Aaron; Kaiser, Maximilian; Pfletschinger, Thilo; Voigt, Kai-Ingo (3DSE Expertenforum 2018 "Digitale Produkte und Geschäftsmodelle", 2018)

Strategic Relevance of Dynamic Capabilities and its Influence on New Product Development in Turbulent Environments: Evidence from German Mechanical Engineering Industry - Vučković, Daliborka; Voigt, Kai-Ingo; Nitsche, J. (International Association for Management of Technology (IAMOT) Conference, 2013)
LIM::291

Towards a Conceptual Exploitation of the Web 2.0 Potential for Sustainable User-Centric Innovation in New Service Development - Vučković, Daliborka; Ernst, Markus; Voigt, Kai-Ingo (ISES Global Conference on Service Excellence, 2010)
LIM::237

What Takes the Wind out of Their Sails? A Micro-Foundational Perspective of Challenges for Building Dynamic Capabilities Towards Digital Business Model Innovation - Witschel, Daliborka; Müller, Julian; Voigt, Kai-Ingo (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung, 2023)
While dynamic capabilities (DCs) are recognized as an important enabler of digital transformation, research lacks knowledge about the underlying challenges and adequate responses of building these capabilities. More specifically, this study aims to shed light into successful digital business model innovation (BMI) by adopting a micro-foundational approach that covers both challenges and successful measures on this path for incumbent industrial firms. Therefore, six case studies building on qualitative empirical research are analyzed that either focus on Internet of Things (IoT)-driven platform BMI or software as a service (SaaS) BMI. The results offer a variety of insights regarding challenges and respective responses. These findings are attributed to DCs and its subdimensions of sensing, seizing and transforming, further revealing the interplay of various factors for specific contexts. Additionally, the study reveals that many challenges and thus required responses are the result of individuals, processes, and structures.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Digital Business Model Innovation; Digital Platforms; Digital transformation; Dynamic capabilities; L00; M10; M19; O32; O33; Micro-foundations; Qualitative Empirical Research